Exhaled breath condensate magnesium levels of infants with bronchiolitis - Fatma Gül Demirkan; Erkan Yılmaz; Melih Hangül; Didem Öztürk; Hasan Demirkan; Mustafa Soylak; Mehmet Köse (The Turkish Journal of Pediatrics, 2018)
The aim of this study is to determine the exhaled breath condensate (EBC) magnesium levels of infants with bronchiolitis and to investigate their relationship with disease severity. Fifty infants with moderate and severe bronchiolitis, grouped according to the bronchiolitis clinical severity scores (CSS), and 25 healthy children were included in the study. EBC was collected using an R tube commercial device; flammable atomic absorption spectrometry was used for the identification of magnesium level in this method. The median concentration of EBC magnesium levels in the group of moderate bronchiolitis patients was 0.82 (0-2.71) μg/ml, and that of severe bronchiolitis patients was 0.57 (0-3.16) μg/ml. The median concentration of EBC magnesium levels in the control group was 0.45 (0.06-2.66) μg/ml. There were no significant differences among the three groups (p > 0.559). The magnesium levels of the two bronchiolitis groups were also found in a wide range. In conclusion, EBC magnesium levels were not different in bronchiolitis patients and do not reflect disease severity.